PENGGUNAAN CERITA BERGAMBAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS VI A MI ABU HURAIRAH MAKASSAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of using illustrated stories in improving the reading skills of sixth-grade (A) students at Abu Hurairah Elementary School in Makassar. The researcher employed a classroom action research method through observation, testing, and document analysis. The results of the study indicate that the use of illustrated stories in improving reading skills showed a significant improvement. In the first cycle, the students’ achievement reached 38%, which was categorized as “low,” and then increased in the second cycle to 100%, which was categorized as “excellent.” This demonstrates a substantial improvement in students’ reading skills. Furthermore, the observation results revealed that both teacher and student activities were well executed. The teacher demonstrated strong competence in conducting the teaching and learning process, while the students showed high enthusiasm during the learning activities using illustrated stories. These findings indicate that the use of illustrated stories is highly effective in improving and developing students’ reading skills and can be recommended as an appropriate method for teaching the Arabic language.